2012
DOI: 10.1017/s0022149x12000065
|View full text |Cite
|
Sign up to set email alerts
|

A comparison ofToxocara canisembryonation under controlled conditions in soil and hair

Abstract: Toxocara spp. eggs require a period of time under appropriate environmental conditions to become infective to definitive and paratenic hosts. Temperature and humidity are important factors known to affect the levels of development in soil. We aimed to investigate whether the eggs of T. canis could embryonate in dog hair under controlled conditions of temperature and humidity and, if so, to what degree. No previous work had been carried out on embryonation in hair under controlled conditions. Soil samples expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 20 publications
0
23
0
1
Order By: Relevance
“…It has been demonstrated that Toxocara spp. egg can embroyonate in the coats of dogs, but it is not at as high rate as in soil [25]. Toxocara eggs are long-lived in the environment and, without effective treatment of egg-shedding dogs and cats, numbers of infective eggs will increase in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Toxocara spp. egg can embroyonate in the coats of dogs, but it is not at as high rate as in soil [25]. Toxocara eggs are long-lived in the environment and, without effective treatment of egg-shedding dogs and cats, numbers of infective eggs will increase in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases caused by soil-transmitted helminths (STHs) are important diseases of humans which affect about one-third of the world's population. From the public health perspective, soil examination is an effective substitute for faecal examination in epidemiological surveys of STH infection [10][11][12][13][14][15][16]. Earthworms may be play a significant role in transmitting the eggs in soils [17], as well as flies [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…According to Cardoso et al [ 17 ], the domestic slaughtering of pigs and small ruminants showed a statistical association with Toxocara infections, and this practice is usual in farm dog owners in this municipality. Human infection is caused by direct contact with contaminated soil or dog hair [ 59 ]. Visceral larva migrans , ocular larva migrans [ 60 ], and severe diseases affecting the central nervous system and/or the eye can occur [ 61 ].…”
Section: Discussionmentioning
confidence: 99%